An infinitely differentiable model for deploying parachutes. (21st January 2021) - Rodrigues, H; Soares, A L; dos Santos, A C; de Pinho, M O
Abstract: In this article, we identify a general structure for the drag force that acts on a model rocket equipped with a parachute. This structure makes use of functions that promote a continuous transition between different magnitudes of the drag force. The kinematics of this system is discussed for some concrete transition functions with the intention to arrive at a continuously differentiable model.